2021
DOI: 10.1093/gerona/glab010
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Presynaptic Inhibition During Gait Initiation

Abstract: Age-related changes in presynaptic inhibition (PSI) have not been observed during gait initiation, which requires anticipatory postural adjustment (APA). As APA is centrally modulated and is impaired in older compared to young adults, here we aimed to study the presynaptic control and co-contraction levels in the ankle muscles during gait initiation in older compared to young adults. Fifteen older (age range 65–80 years) and 15 young adults (age range 19–30 years) performed a gait initiation task on a force pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…What are the possible mechanisms underlying delayed APAs seen with ageing? Work has shown increased presynaptic inhibition in spinal circuits prior to gait initiation (i.e., during APAs) in older adults compared with young adults and levels of the inhibition correlating with amplitudes of APAs (Filho et al, 2021). Other studies also reported age differences in the modulation of presynaptic inhibition during an upper-limb postural task (Baudry et al, 2010) and standing (Degani et al, 2020).…”
Section: Corticospinal Excitability and Apas In The Elderlymentioning
confidence: 99%
“…What are the possible mechanisms underlying delayed APAs seen with ageing? Work has shown increased presynaptic inhibition in spinal circuits prior to gait initiation (i.e., during APAs) in older adults compared with young adults and levels of the inhibition correlating with amplitudes of APAs (Filho et al, 2021). Other studies also reported age differences in the modulation of presynaptic inhibition during an upper-limb postural task (Baudry et al, 2010) and standing (Degani et al, 2020).…”
Section: Corticospinal Excitability and Apas In The Elderlymentioning
confidence: 99%
“…Regarding the second question, we agree that restoring PSI may compensate for supraspinal dysfunction during FOG episodes, as we have recently demonstrated that healthy elderly individuals have higher PSI levels associated with weaker APAs compared to healthy young individuals (Filho et al 2021). The increase in PSI levels in elderly individuals has been considered an adaptive/compensatory phenomenon, due to age-related deterioration of supraspinal modulation (Morita et al 1995;Filho et al 2021). It is important to highlight that although we assessed PSI in the ON-medication state during no FOG episodes, we will test the hypothesis that the loss of PSI is greater during OFF-medication state than in ON state, as levodopa changes the excitability of the H-reflex in PD (McLeod & Walsh, 1972).…”
mentioning
confidence: 70%
“…Regarding the second question, we agree that restoring PSI may compensate for supraspinal dysfunction during FOG episodes, as we have recently demonstrated that healthy elderly individuals have higher PSI levels associated with weaker APAs compared to healthy young individuals (Filho et al . 2021). The increase in PSI levels in elderly individuals has been considered an adaptive/compensatory phenomenon, due to age‐related deterioration of supraspinal modulation (Morita et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, using tendon vibration and D1 inhibition, Butchart et al (1993) and Earles et al (2001) reported a decrease in Ia presynaptic inhibition in older adults for the soleus. However, others found no difference in Ia presynaptic inhibition between young and older adults in upper and lower limb muscles (Baudry et al 2010;Baudry and Duchateau 2012;Filho et al 2021). These divergent results do not support Ia presynaptic inhibition as a primary contributor to the lesser H-reflex amplitude in older adults.…”
Section: H Reflex and Chronic Neuromuscular Changes: The Example Of A...mentioning
confidence: 98%